20-MST and PWC170 validity in non-Caucasian children in the UK. Issue 1 (March 1992) - Mahoney, C
Abstract : The validity was investigated of 20-MST (20 Metre Endurance Shuttle Run Test) and PWC170 (Physical Working Capacity) field tests with laboratory-measured peak oxygen uptake (VO2peak) in a multiracial UK population of 12-year olds: 103 subjects completed the 20-MST and 96 of these completed the PWC170. To assess validity, a laboratory treadmill test was completed by ten boys and ten girls who had performed both field tests. VO2peak was 43.8 ml kg-1 min-1 for boys and 38.5 ml kg-1 min-1 for girls. Pearson product-moment correlation showed 20-MST to be a reliable measure of cardiorespiratory fitness (r = 0.83, boys; r = 0.76, girls, P less than 0.03), while correlations with PWC170 were lower (r = 0.64, boys; r = 0.54, girls) and not significant. The 20-MST was consistent in retest (n = 20) - reliability coefficients r = 0.73, boys; r = 0.88, girls; P less than 0.01. The results suggest 20-MST is a valid, measure of fitness in this population when compared with VO2peak. PWC170 is less valid, possibly due to cultural and social backgrounds. The cycle test was inappropriate in this population, especially for girls unaccustomed to exercise and cycling. The 20-MST test is recommended for large groups of children when facilities are limited. It requires limited skill or habituation and is relatively non-invasive.